Grammatical and Lexical Cohesion in Indonesian EFL Argumentative Essays - Septiana Wandira; La Ode Achmad Suherman; Dwi Nur Hadiyansah W.S. (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
This study investigates grammatical and lexical cohesion in Indonesian EFL undergraduates’ argumentative essays and examines how cohesion relates to writing quality. A small learner corpus of 15 timed essays was manually coded for reference, articles, conjunctions, and lexical reiteration following Halliday and Hasan’s framework, and rated with an analytic rubric. Descriptive statistics and Spearman correlations were complemented by qualitative analysis of higher- and lower-rated texts. Quantitative results show frequent use of articles, basic conjunctions, and lexical repetition, but cohesion indices display weak, sometimes negative, associations with overall and coherence scores. Qualitative findings reveal that stronger essays are characterised by stable reference chains, a wider range of logical connectives, and purposeful lexical reiteration, whereas weaker texts rely on broken chains and mechanical repetition. The study argues that cohesion quality, rather than quantity, is more salient for raters and discusses implications for genre-based EFL writing instruction.